ARENA (KRITIK) SASTRA INDONESIA: STUDI KASUS PADA JURNAL POETIKA FIB UNIVERSITAS GADJAH MADA - Dharma Satrya HD. (Literary Studies, Faculty of Cultural Sciences, Universitas Gadjah Mada, 2015)
Abstrack This paper discusses the journal as an arena for literary criticism. In the journal the practice of legitimacy is occurred, as a writer, critics or academics. Taking and making positions are conducted by the agents of the journal. This study found that in Jurnal Poetika, academics legitimize the writer and conversely the writer who became the academics legitimize the other writer and even criticize the other academics in their different arena, and it is also possible in the same arena. In the arena of criticism, the exchange of positions continues as long as the existence of the arena, depends on the authorities of the arena, with Faruk as the agent of symbolic power, and even the power is identical to himself. In the arena (criticism) of Indonesian literature especially in the University of Gadjah Mada, Faruk brings the arena (criticism) of Indonesian literature to a new direction with a new angle to bring the literary text towards newer perspective that is identical to the newer view which is a part of the habitus in Indonesian literature.Keywords: Arena, Practice, Positions.